1984
DOI: 10.1159/000215063
|View full text |Cite
|
Sign up to set email alerts
|

Studies on PIVKA VII

Abstract: In 30 subjects on stabilized oral anticoagulant treatment, factor VII activity (VII:C) and factor VII antigen (VIl·Ag) were evaluated. The average VII:C and VIl·Ag levels were 8.7 and 30.7, respectively. All plasma samples were treated with 1 M barium chloride: all the activity and a corresponding average amount of antigen were adsorbed by the salt. The cold-promoted activation of factor VII was found in 5/30 subjects. Corresponding amounts of VII:C and VII: Ag were also removed from the plasma of these subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1986
1986
1987
1987

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…C appears to reflect a decrease of synthesis of the protein, in association with reduced levels of the other vitamin K-dependent proteins. In long-term dicoumarol-treated patients, the discrepancy between F VII Ag and F VII C is in favor of the presence of a-and/or hypocarboxylated molecules as previously reported for F VII (24)(25)(26), and for other vitamin K-dependent proteins (16-30). In two patients tested at the onset of anticoagulant therapy, there was a rapid disappearance of both F VII and protein C antigens, indicating a similar short (5-7 h) half-life for both proteins, in accordance with another report (31).…”
Section: Discussionsupporting
confidence: 76%
“…C appears to reflect a decrease of synthesis of the protein, in association with reduced levels of the other vitamin K-dependent proteins. In long-term dicoumarol-treated patients, the discrepancy between F VII Ag and F VII C is in favor of the presence of a-and/or hypocarboxylated molecules as previously reported for F VII (24)(25)(26), and for other vitamin K-dependent proteins (16-30). In two patients tested at the onset of anticoagulant therapy, there was a rapid disappearance of both F VII and protein C antigens, indicating a similar short (5-7 h) half-life for both proteins, in accordance with another report (31).…”
Section: Discussionsupporting
confidence: 76%
“…More specific tests are required to demonstrate vitamin K deficiency, such as the measurement of abnormal, noncarboxylated prothrombin by enzyme-linked sandwich immuno-assay, using a monoclonal antibody against this abnormal prothrombin (11,12). Determination of the concentration of other precursor proteins (PIVKA, IX, X, VII) by specific antibodies could give additional information (10,14).…”
Section: Discussionmentioning
confidence: 99%
“…Based on reactivity with different thromboplastins, Girolami et al [2][3][4][5] and Girolami [6] reported three activa tion variants: Padua 1, Padua 2 and Verona. On the other hand, using a neutralization assay several molecular variants of FVII were described [7], Mariani et al [8][9][10] clas sified FVII deficiency according to the rela tionship between FVII coagulant activity (FVIIC) and FVII related antigen (FVIIAg) levels, and established three immunological variants: VII-, VII+, and VIIR.…”
Section: Introductionmentioning
confidence: 99%